Inhibition of the Sec61 translocon overcomes cytokine‐induced glucocorticoid resistance in T‐cell acute lymphoblastic leukaemia. (17th April 2022) - Meyer, Lauren K.; Delgado‐Martin, Cristina; Sharp, Phillip P.; Huang, Benjamin J.; McMinn, Dustin; Vincent, Tiffaney L.; Ryan, Theresa; Horton, Terzah M.; Wood, Brent L.; Teachey, David T.; Taunton, Jack; Kirk, Christopher J.; et al.
Abstract: Glucocorticoid (GC) resistance is a poor prognostic factor in T‐cell acute lymphoblastic leukaemia (T‐ALL). Interleukin‐7 (IL‐7) mediates GC resistance via GC‐induced upregulation of IL‐7 receptor (IL‐7R) expression, leading to increased pro‐survival signalling. IL‐7R reaches the cell surface via the secretory pathway, so we hypothesized that inhibiting the translocation of IL‐7R into the secretory pathway would overcome GC resistance. Sec61 is an endoplasmic reticulum (ER) channel that is required for insertion of polypeptides into the ER. Here, we demonstrate that KZR‐445, a novel inhibitor of Sec61, potently attenuates the dexamethasone (DEX)‐induced increase in cell surface IL‐7R and overcomes IL‐7‐induced DEX resistance.